Implementation of the First Come First Served Method in a Website-Based Sports Facility Reservation Service System - Rangkuti, Irsan Efendi; Taufiq, Taufiq; Suwanda, Rizki (International Journal of Engineering, Science and Information Technology, 2025)
The people of Kotanopan have a high interest in sports such as futsal and badminton, an interesting phenomenon that shows the popularity of these sports and opens up many business opportunities. Most sports facilities for rent still use a conventional system where prospective renters must come directly to the field or call the manager to make a reservation, making it prone to errors in the reservation process. From the management's side, they often encounter obstacles when processing tenant reservations, especially when sorting the schedules that the tenants have created. This research aims to build a sports facility reservation service system using the First Come, First Served (FCFS) method. This method is the most suitable scheduling system for the sports facility reservation system in Kotanopan. The results of the First Come First Served (FCFS) method experiment with a random trial of 5 users, each with execution times of 3, 3, 5, 5, and 9, yielded an average waiting time of 1 minute and an average reservation completion time of 6. With the test results showing that the system can meet the needs and has functions accessible to every system user, it is hoped that this system can facilitate users in making reservations online.